Analisis Perhitungan Tegangan Eksiter Untuk Menghasilkan Tegangan Generator 6,3 kV Kondisi Tanpa Beban Pada Mesin ZV PLTD Ampenan - Ida Ayu Sri , Adnyani; Michael Jonathan M (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING, INFORMATION TECHNOLOGY, CONTROL ENGINEERING, AND ROBOTIC), 2025)
Analysis of the excitation voltage required to produce an output voltage of 6.3 kV on the ZV-type synchronous generator, Unit 2, at PLTD Ampenan under no-load conditions. The stability of the generator's output voltage is significantly influenced by the excitation voltage, which is regulated through the Automatic Voltage Regulator (AVR) system. The study was conducted using two approaches: direct field measurements and a mathematical approach based on the magnetic induction voltage formula. Field measurements indicated that the average excitation voltage required was 7.24 VDC, while the mathematical approach yielded a value of 7.7 VDC. This discrepancy is attributed to the use of assumed parameters, such as the number of windings on the stator and rotor, as well as the omission of certain technical factors, including temperature, impedance, reactance, and voltage losses. This analysis aims to provide a technical understanding of the influence of excitation voltage on generator performance and to serve as a foundation for controlling and maintaining the excitation system to ensure that the generator's output voltage remains stable. It is expected that this study will support the reliability of power supply at PLTD Ampenan and serve as a technical reference in the operation of synchronous generators.